Attitudes to and Experiences of Physical Activity After Colon Cancer Diagnosis Amongst Physically Active Individuals – A Qualitative Study. (4th August 2022) - Renman, David; Strigård, Karin; Palmqvist, Richard; Näsvall, Pia; Gunnarsson, Ulf; Edin-Liljegren, Anette
Background: Physical activity improves survival, reduces postoperative complications, and reduces the risk of developing colon cancer. It is important to maintain physical activity after receiving a diagnosis of colon cancer to improve postoperative recovery. Individuals who are physically active and diagnosed with colon cancer presumably have different motivations to maintain physical activity compared to their sedentary counterparts. Objective: Enlighten how the diagnosis of colon cancer might affect physically active individuals in their attitude and experiences towards physical activity. Methods: A qualitative study using content analysis was conducted in northern Sweden based on semi-structured telephone interviews of twenty patients diagnosed with colon cancer. All participants met the recommendations for physical activity issued by the World Health Organization. Results: Participants were between 50 and 88 years and 50% were male. Three main categories were identified: I'll fight the cancer and come out stronger; The diagnosis makes no difference; and The diagnosis is an obstacle for physical activity. These main categories represent the ways the individuals reacted to the diagnosis of colon cancer regarding their physical activity. Conclusion: Attitudes to and experience of physical activity after colon cancer diagnosis varied from a will to increase physical activity and fight the cancer, to the diagnosis putting a stop to physical activity. It is important that healthcare professionals recommend physical activity even in already physically active individuals, to encourage continued physical activity after diagnosis of colon cancer.